Trade unionism under collective bargaining : a theory based on comparisons of six countries - Clegg, Hugh Armstrong (Basil Blackwell OxfordGB, 1983)
Develops and expounds a theory of trade union behaviour under collective bargaining based on and tested by evidence from Australia, France, Sweden, the United Kingdom, the United States of America, and West Germany. Discusses and analyzes variations from one country to another of union membership, structure, government, workplace organization, strikes, industrial democracy and political action.